The import tariff changes and sectoral production in Turkey: a computable general equilibrium (CGE) modeling approach - Hüseyin T. Eğen (Quantitative Finance and Economics, 2019)
From the point of increasing trade liberalization policies worldwide, this study aims to test the effects of the changes in import tariffs in Turkey. For that purpose, we benefit from simultaneous equations based on a computable general equilibrium framework. We construct an updated social accounting matrix for Turkey which is compatible with our model by using different data sources. Our findings obtained from the model suggest that import tariff increase will provide increases in domestic production after each subsequent tariff rate reductions. Furthermore, increasing domestic production associates with improvements in trade deficits and employment. So, tariff-distorted effects of trade policy as such are said to be small in Turkey.